Islamic Education Curriculum Management in Shaping Student Character at SDIT Birrul Walidain Central Lampung - Cipto Handoko (PT. Pusmedia Group Indonesia, 2025)
This research aims to describe how the management of Islamic education curriculum is implemented in shaping students' character at SDIT Birrul Walidain. The Islamic education curriculum not only focuses on cognitive aspects but also emphasizes character development through the integration of Islamic values in all learning activities and the school culture. This research employs a descriptive qualitative approach with data collection techniques such as interviews, observations, and documentation. The informants in this study consist of the principal, classroom teachers, Islamic Education teachers, students, and parents of students. The results show that curriculum management is conducted in a structured manner from the planning, implementation, to evaluation stages. The curriculum planning is carried out through an annual working meeting involving all teachers and school staff. The implementation of the curriculum is carried out by integrating Islamic values into each subject and through habituation programs such as dhuha prayers, Quran recitation, and memorization. Student character evaluation is conducted periodically through behavioral observation, character control books, and communication with parents. In addition, the school's religious culture, the involvement of the principal as a spiritual leader, and synergy with parents also strengthen the effectiveness of the curriculum in shaping students' character. Thus, the management of the Islamic education curriculum at SDIT Birrul Walidain has proven to effectively shape students' character holistically, although challenges such as time limitations and the need to improve collaboration between the school and parents still exist.